Heterogeneous Supersaturation in Mixed Perovskites. Issue 7 (8th February 2020) - Tan, Chih Shan; Hou, Yi; Saidaminov, Makhsud I.; Proppe, Andrew; Huang, Yu Sheng; Zhao, Yicheng; Wei, Mingyang; Walters, Grant; Wang, Ziyun; Zhao, Yongbiao; Todorovic, Petar; Kelley, Shana O.; et al.
Abstract: Thin‐film solar cells based on hybrid lead halide perovskites have achieved certified power conversion efficiencies exceeding 24%, approaching those of crystalline silicon. This motivates deeper studies of the mechanisms that determine their performance. Twin defect sites have been proposed as a source of traps in perovskites, yet their origin and influence on photovoltaic performance remain unclear. It is found that twin defects—observed herein via both transmission electron microscopy and X‐ray diffraction—are correlated with the amount of antisolvent added to the perovskite and that twin defects in the highest‐performing perovskite photovoltaics are suppressed. Heterogeneous supersaturation nucleation is discussed as a contributor to efficient perovskite‐based optoelectronic devices. Abstract : Twin defect sites are proposed as a source of traps in perovskites, yet their origin and influence on photovoltaic performance remain unclear. Here, it is found that twin defects are influenced by the antisolvent amount added to the perovskite, a finding seen both via transmission electron microscopy and X‐ray diffraction. Twin defects in the highest‐performing perovskites are suppressed.